The Effect of Social Media on Spreading Cosmetic Surgery in the Saudi Society from University Female Students' Point of View (Journal of Namibian Studies : History Politics Culture, 2023)
This study is an exploratory study which aimed to identify the effect of social media on spreading cosmetic surgeries in the Saudi society, address the widespread of cosmetic surgeries in the Saudi society, identify the reasons for accepting cosmetic surgeries, and the consequences of their spread within Saudi society. To achieve these objectives, an analytical descriptive approach was used as being suitable for the nature of the study. A purposive sample of students of Collage of Arts at Imam Abdulrahman bin Faisal University in Dammam in the Eastern Region of Saudi Arabia was selected. A number of findings were revealed in this study, notably: social media affected the spread of cosmetic surgeries in the Saudi society greatly; and cosmetic surgeries could promote social integration and improve individuals' social relationships. Finally, a number of recommendations were introduced, notably: improving the aesthetic culture of society, promoting values of self-confidence and selfsatisfaction, and disregarding others' views of body appearance and focusing on personal health.